Bank leverage, credit and GDP in Switzerland: A VAR analysis 1987-2015 - Peter Kugler; Georg Junge (University of Basel, Center of Business and Economics (WWZ), 2017)
A VAR analysis of Swiss data from 1987 to 2015 provides no evidence for significant long and short run influence of leverage on GDP, credit and the interest rate spread. Increasing capital requirements for banks should therefore have no strong negative macroeconomic effects.
Keywords: G21; G28; 330; GDP; credit; leverage interest spread; long and short run impact VAR